The Study of Causal Factors of Students with Learning Disabilities’ Academic Achievement in Inclusive Classroom - Subsandee, Pannarai; Kongtong, Ausa (Ratchaphruek Journal, 2014)
The objective of the study in the casual factors of academic achievement of students with learning disabilities forinclusive classroom is to study the casual factors of academic achievement of students’ learning disabilities in inclusive classroom. The sample group was 440 students selectedbyusing LISREL analysis criteria. The instrument was questionnairethat revealed the effectfactorsof academic achievement of learning disabled students’ and the reliability of the questionnaire was .98. The research result using structural model and exploratory analysis by LISREL program version 9.1 code: 823F-C5B0-8545-B412, found that; the teacher factors has significantly affected to the academic achievement at .05, and affected to the students factors at 0.01. The teacher factors and the environment factors are significantly affected to the curriculum factors at .01. This study found that the teachers’ factors were significant, itstatistically affected to the academic achievement, the students factor and the curriculum factor.